Penerapan Model Pembelajaran Student Team Achievement Division pada Pembelajaran IPA Mahasiswa PGSD STKIP Al Hikmah Surabaya - Adhy Putri Rilianti; Misbachul Huda (Program Studi Pendidikan Guru Sekolah Dasar STKIP Al Hikmah Surabaya, 2020)
Abstract This study aims to describe the Student Team Achievement Division (STAD) learning model in Science. It is applied to PGSD STKIP Al Hikmah Surabaya students. The research used a descriptive qualitative method. Data was collected by test and observation. Data was analyzed by qualitative analysis. This research result showed that the STAD learning model can be implemented in Science learning at PGSD STKIP Al Hikmah Surabaya, especially to learn Animal Organ Systems and Animal Life Cycles. Learning plan for applying the STAD learning model was started by designing lesson plans and preparing some platforms of online learning. The syntax of STAD learning model was 1) Students were divided by some groups of 3, 2) Students discussed, 3) Students created a mind mapping, 4) Students presented their discussion result, 5) Students responded to other group performance, 6) Students took individual quiz, 7) Students and lecturer discussed the quiz, 8) Students calculated the individual progress score, and 90 Students received the team recognition. We had to check the internet signal connection if we wanted to implement the STAD learning model that was implemented in online learning so that the learning process held well. Abstrak Tujuan penelitian ini adalah untuk menggambarkan pelaksanaan penerapan model pembelajaran Student Team Achievement Division (STAD) pada Pembelajaran IPA Mahasiswa PGSD STKIP Al Hikmah Surabaya. Metode penelitian yang digunakan yaitu kualitatif deskriptif. Data dikumpulkan menggunakan teknik tes dan observasi. Analisis data yang digunakan yaitu kualitatif. Hasil penelitian ini menunjukkan bahwa model pembelajaran STAD dapat diterapkan pada Pembelajaran IPA Mahasiswa PGSD STKIP Al Hikmah Surabaya, khususnya pada materi Sistem Organ dan Daur Hidup Hewan. Perencanaan penerapan pembelajaran STAD dilakukan dengan menyusun RPP dan menyiapkan platform pembelajaran daring. Langkah-langkah penerapan STAD, antara lain 1) Mahasiswa dibagi menjadi beberapa kelompok dengan anggota 3 orang, 2) Mahasiswa berdiskusi, 3) Mahasiswa membuat mind mapping sebagai hasil diskusi, 4) Mahasiswa mempresentasikan hasil diskusinya, 5) Mahasiswa saling menanggapi penampilan kelompok, 6) Mahasiswa mengerjakan kuis individual, 7) Mahasiswa bersama dosen membahas kuis individual, 8) Mahasiswa menghitung skor kemajuan individu, dan 9) Mahasiswa menerima rekognisi tim. Pembelajaran STAD yang dilaksanakan secara daring perlu memperhatikan kestabilan sinyal internet agar pembelajaran dapat berlangsung dengan lancar.